Magnetic resonance imaging signs of high intraventricular pressure - comparison of findings in dogs with clinically relevant internal hydrocephalus and asymptomatic dogs with ventriculomegaly - Laubner, Steffi; Ondreka, Nele; Failing, Klaus; Kramer, Martin; Schmidt, Martin J.; Justus Liebig University Giessen (My University, 2015)
Background: Magnetic resonance imaging (MRI) findings of canine brains with enlarged ventricles in asymptomatic dogs were compared to those in dogs with clinically relevant internal hydrocephalus, in order to determine the imaging findings indicative of a relevant increase in intraventricular pressure. Discrimination between clinically relevant hydrocephalus and ventriculomegaly based on MRI findings has not been established yet and is anything but trivial because of the wide variation in ventricular size in different dog breeds and individuals. The MRI scans of the brains of 67 dogs of various breeds, skull conformation and weight were reviewed retrospectively. Based on clinical and imaging findings, the dogs were divided into three groups: a normal group (n=20), a group with clinically silent ventriculomegaly (n=25) and a group with severe clinically relevant internal hydrocephalus (n=22). In addition to the ventricle/brain-index, a number of potential subjective signs of increased intraventricular pressure were recorded and compared between the groups. Results: The ventricle/brain-index was significantly higher in dogs with relevant hydrocephalus (p<0.001) and a threshold value of 0.6 was specified as a discriminator between internal hydrocephalus and ventriculomegaly. Other MR imaging findings associated with clinically relevant hydrocephalus were an elevation of the corpus callosum (p<0.01), dorsoventral flattening of the interthalamic adhesion (p<0.0001), periventricular edema (p<0.0001), dilation of the olfactory recesses (p<0.0001), thinning of the cortical sulci (p<0.0001) and/or the subarachnoid space (p<0.0027) and disruption of the internal capsule adjacent to the caudate nucleus (p<0.0001). Conclusion: A combination of the abovementioned criteria may support a diagnosis of hydrocephalus that requires treatment.
Keywords: hydrocephalus; ventriculomegaly; dog; intraventricular pressure; brain malformation; ddc:630